2020
DOI: 10.1021/jacsau.0c00038
|View full text |Cite
|
Sign up to set email alerts
|

Water Triggered Synthesis of Highly Stable and Biocompatible 1D Nanowire, 2D Nanoplatelet, and 3D Nanocube CsPbBr3 Perovskites for Multicolor Two-Photon Cell Imaging

Abstract: Two-photon imaging in the near-infrared window holds huge promise for real life biological imaging due to the increased penetration depth. All-inorganic CsPbX 3 nanocrystals with bright luminescence and broad spectral tunability are excellent smart probes for two-photon bioimaging. But, the poor stability in water is a well-documented issue for limiting their practical use. Herein, we present the development of specific antibody attached water-resistant one-dimensional (1D) CsPbBr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
119
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(121 citation statements)
references
References 70 publications
1
119
0
1
Order By: Relevance
“…Significant MPA strength, along with good photostability, also makes perovskite materials with great potential for OL, bioimaging and so on. [133,[149][150][151][152][153] As reported by Li et al, the composition of SiO 2 @CsPbBr 3 QDs exhibited 50% OL at 1.68 J cm −2 for the nanosecond regime, and 74% OL at 0.1 J cm −2 for the picosecond regime at 532 nm. [149] Varma et al demonstrated the (BA) 2 (MA)Pb 2 I 7 (I n=2 ) QDs showed more than 50% OL at 85 μJ for 5 ns, 532 nm Neodyminum-doped YttriumAlumini-umGarnet (Nd-YAG) laser pulses.…”
Section: Other Applicationsmentioning
confidence: 89%
See 1 more Smart Citation
“…Significant MPA strength, along with good photostability, also makes perovskite materials with great potential for OL, bioimaging and so on. [133,[149][150][151][152][153] As reported by Li et al, the composition of SiO 2 @CsPbBr 3 QDs exhibited 50% OL at 1.68 J cm −2 for the nanosecond regime, and 74% OL at 0.1 J cm −2 for the picosecond regime at 532 nm. [149] Varma et al demonstrated the (BA) 2 (MA)Pb 2 I 7 (I n=2 ) QDs showed more than 50% OL at 85 μJ for 5 ns, 532 nm Neodyminum-doped YttriumAlumini-umGarnet (Nd-YAG) laser pulses.…”
Section: Other Applicationsmentioning
confidence: 89%
“…By taking advantages of significant MPA strength, perovskite materials are desirable for a variety of technological applications. Among them, upconversion lasing, [130,131] sub-band photodetection, [58,132] and high-resolution bioimaging [133,134] have been demonstrated with great potentials for optoelectronic and biophotonic systems.…”
Section: Perovskite-based Mpa Applicationsmentioning
confidence: 99%
“…The record of photoluminescence and electroluminescence efficiency 216 of 2D perovskites has continuously been broken in display, encryption, biological imaging and X-Ray detection. 52,217,218 For instance, Chandra et al 219 reported the use of specific antibody attached water-resistant CsPbBr 3 nanocrystals in different dimensions for two-photon imaging of breast cancer cells in the near IR region, superior to conventional organic fluorescence labels.…”
Section: Perspectivesmentioning
confidence: 99%
“…A good example of that new emerging application of perovskites is the recent report by Pramanik and co-workers who developed fully biocompatible CsPbBr 3 nanomaterials with different morphologies by coating them with amine-poly(ethylene glycol)-propionic acid. [63] A traditional approach to functionalization of perovskite surface with biocompatible agents would be the exchange of the existing hydrophobic ligands on CsPbBr 3 surface to a biological surfactant along with transfer to the aqueous medium. Instead, a more complex strategy was employed which rests on the synthesis of non-luminescent 0D Cs 4 PbBr 6 NCs using hot injection method, followed by treatment with water of these NCs Adv.…”
Section: Two-photon Imagingmentioning
confidence: 99%